A-82 Neurocognitive Improvement after Intra-Arterial Bevacizumab for Steroid-Refractory Radiation Necrosis of the Brain. (30th August 2021) - Folley, Bradley S; Kadner, Robert J; Sheehan, Jason P; Han, Dong Y; Kryscio, Richard J; Carter, Mary B; Shields, Lisa B E; Plato, Brian M; La Rocca, Renato V; Spalding, Aaron C; Yao, Tom L; Fraser, Justin F; et al.
Abstract: Objective: Evaluate neurocognitive change after single low-dose targeted intra-arterial (IA) bevacizumab in patients with brain radiation necrosis. Methods: Phase II, single-arm, prospective trial. 10 adults underwent targeted 2.5 mg/kg IA bevacizumab. Neurocognitive indices (Neuropsychological Assessment Battery® and Wechsler Test of Adult Reading) were measured at baseline and 12-months to document performance in 5 domains: Attention, Language, Learning and Memory, Visuospatial, and Executive Function. Clinical indices also quantified. Data (mean ± SD, 95% confidence interval [CI], Cohen's d) were analyzed using paired t tests. Null hypothesis rejected for p < 0.05. Results: At baseline, Numbers-&-Letters Speed T-score (38.2 ± 10.7) indicated decreased processing speed consistent with sub-cortical pattern of illness. All other baseline neurocognitive indices were within normalized means (image). 12-months post-treatment, Numbers-&-Letters Errors T-score increased by 6.0 ± 4.9 [95%CI 1.9, 10.1] (t = 3.464, d = 1.225, p = 0.010). List-Learning List-Long-Delayed-Recall T-score increased by 9.0 ± 5.6 [95% CI 4.3, 13.7] (t = 4.520, d = 1.598, p = 0.003) and Design-Construction T-score increased by 3.5 ± 4.1 [95%CI 0.04, 7.0] (t = 2.391, d = 0.845, p = 0.048). Volume of radiation necrosis decreased by 74.4 ± 14.7% (t = −3.308, d = 1.169, p = 0.013). Headache decreased by 84.4 ± 18.2% (t = −3.495, d = 1.236, p = 0.010). 0/10 died or exhibited AEs attributed to bevacizumab. 2/10 patients experienced radiation necrosis recurrence at months 10 and 11, respectively. Conclusions: Single low-dose intra-arterial targeted bevacizumab led to durable neuropsychological performance increase in memory retrieval and visuospatial ability consistent with improvement in sub-cortical function. To our knowledge this is the first prospective report of this novel approach in adults. Clinical improvements mirrored neuropsychologic improvements. Randomized trials are needed comparing targeted low-dose IA bevacizumab to multi-cycle IV bevacizumab at higher doses to determine which is best alternative in brain radiation necrosis.